SAT0197 Treatment outcomes with anti-tnf and non-anti-tnf disease-modifying therapy by baseline body mass index. (15th June 2017) - Alemao, E; Guo, Z; Iannaccone, C; Frits, M; Weinblatt, M; Shadick, N
Abstract : Background: Recent studies have indicated that being overweight or obese could reduce the effect of anti-TNF treatment in patients (pts) with RA. 1, 2 Other data show that certain biologic (b)DMARDs, such as abatacept, work independently of BMI. 3, 4 Additional data on the role of BMI on treatment outcomes in clinical practice settings is required to inform clinical practice. Objectives: To evaluate the impact of BMI on outcomes of disease activity in pts with RA treated with TNF and non-TNF agents (conventional or other bDMARDs). Methods: Pts enrolled in a tertiary care centre RA registry, established in 2003, were analysed. The registry mostly comprises pts with established RA who were evaluated semi-annually for multiple clinical patient-reported outcomes and resource utilization parameters, and annually for composite disease activity measures such as DAS28 (CRP), CDAI and SDAI. The current analysis is based on pts enrolled in the RA registry with BMI values at time of enrolment. Pts were classified into groups based on BMI: normal (BMI <25 kg/m 2 ), overweight (BMI ≥25 to <30 kg/m 2 ) and obese (BMI ≥30 kg/m 2 ). Outcomes evaluated included change from baseline in DAS28 (CRP), CDAI, SDAI and joint counts at 12 months from treatment exposure. Treatments were categorized into TNF and non-TNF, which included conventional DMARDs and other non-TNF biologics. Multivariate linear regression analyses were used to evaluate impact of BMI on treatment outcomes controlling for baseline covariates of age, sex, disease duration, co-morbidities, baseline disease activity and serostatus. Separate models were run for the TNF and non-TNF groups. Results: A total of 997 (78%) pts in the registry had baseline BMI values and were included in the analysis. Around 37% (n=371) had TNF exposure and were included in the TNF cohort; the remainder (63%; n=626) were included in the non-TNF cohort. Proportions of pts in the normal, overweight and obese groups for the TNF cohort were 45.5% (n=169), 27.5% (n=102) and 27.0% (n=100), respectively. For the non-TNF cohort, these were 41.7% (n=261), 33.1% (n=207) and 25.2% (n=158), respectively. In both cohorts, pts with normal BMIs were younger vs the overweight and obese BMI groups. However, obese BMI pts had higher disease activity measures at baseline (mean [SD] CDAI: 22.8 [17.8] for TNF and 24.9 [17.3] for non-TNF) vs the normal BMI pts (17.5 [15.9] for TNF and 19.9 [16.7] for non-TNF) and overweight BMI pts (20.9 [16.5] for TNF and 20.5 [15.0] for non-TNF). Adjusted mean change from baseline in disease activity in the TNF cohort was significantly reduced across all disease activity measures for the normal BMI group (p<0.05), but not for the overweight and obese groups (Fig). There were significant reductions in disease activity measures for all BMI groups (all p<0.05) in the non-TNF cohort (Fig). Conclusions: Independent of BMI, non-anti-TNF therapy demonstrated similar outcomes in pts with RA. However, obese and overweight pts with RA (vs normal weight) had less improvement in disease activity (as measured by DAS28 [CRP]) with anti-TNF therapy. References: Gremese E, et al. Arthritis Care Res 2013;65:94–100. Klaasen R, et al. Arthritis Rheum 2011;63:359–64. Gardette A, et al. Ann Rheum Dis 2015;74:1041. Disclosure of Interest: E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Z. Guo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, C. Iannaccone: None declared, M. Frits: None declared, M. Weinblatt Grant/research support from: Amgen, Bristol-Myers Squibb, Crescendo Biosciences, UCB, DxTerity, Consultant for: Amgen, Bristol-Myers Squibb, Crescendo Biosciences, UCB, AbbVie, Lilly, Pfizer, Roche, N. Shadick Grant/research support from: Bristol-Myers Squibb, UCB, Mallinckrodt, Amgen, Brescendo Biosciences, Consultant for: Bristol-Myers Squibb